1992
DOI: 10.1002/cne.903220410
|View full text |Cite
|
Sign up to set email alerts
|

5′‐Nucleotidase: A new marker for striosomal organization in the rat caudoputamen

Abstract: The distribution of the adenosine-producing ectoenzyme 5'-nucleotidase was studied by means of a histochemical lead technique in the caudoputamen of normal adult rats and of rats in which injections either of 6-hydroxydopamine in the medial forebrain bundle or of ibotenic acid in the caudoputamen had been made 1-3 weeks previously. The patterns of striatal 5'-nucleotidase activity in these animals were compared in serial sections to the patterns of calbindin-D28k immunoreactivity and of 3H-naloxone ligand bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Although it appears as if a subset of neurons can make GDNF following pilocarpine-induced status epilepticus (15), a neuronal localization of synthesis could not be determined in the developing striatum (2). However, GDNF was cloned from a glial cell line (1), and it has been demonstrated that striosomes contain specific subpopulations of glial cells characterized by their content of 5'-nucleotidase (30). It is therefore possible that such a subset of glial cells synthesize GDNF to attract and maintain GDNF-sensitive dopaminergic nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…Although it appears as if a subset of neurons can make GDNF following pilocarpine-induced status epilepticus (15), a neuronal localization of synthesis could not be determined in the developing striatum (2). However, GDNF was cloned from a glial cell line (1), and it has been demonstrated that striosomes contain specific subpopulations of glial cells characterized by their content of 5'-nucleotidase (30). It is therefore possible that such a subset of glial cells synthesize GDNF to attract and maintain GDNF-sensitive dopaminergic nerve terminals.…”
Section: Discussionmentioning
confidence: 99%
“…5′Nucleotidases in particular were found at the surface membranes of axons and dendrites (Bernstein et al, 1978) and are associated with glial membranes in the central nervous system (Schoen & Graybiel, 1992). Localization of ecto-Ca-ATPase and 5′-ectonucleotidase activities was shown in caveolae of smooth muscle cells of the guinea-pig vas deferens and their role in neurotransmission has been suggested (Kittel & Bacsy, 1994).…”
Section: Termination Of Neurotransmitter Actionmentioning
confidence: 99%
“…USA 95 (1998) We used calbindin immunohistochemistry to identify the two compartments in the caudoputamen based on evidence (68) that areas poor in this marker correspond to striosomes͞ patches originally identified as areas that, among other things, are poor in acetylcholinesterase (10, 11) and express opiate receptor binding (11). However, the matrix marker calbindin does not reliably stain the dorsal and lateral sectors of the middle and posterior parts of the caudoputamen in the rat (69), even though these sectors are differentiated into the two compartments by other markers (11,69). Because our ability to locate electrode tips with respect to the compartments was limited to the medial, central, and ventral areas of the caudoputamen, the present analysis is limited to these areas of the caudoputamen.…”
mentioning
confidence: 99%